ANALISIS PERBANDINGAN KINERJA KEUANGAN PT BANK RAKYAT INDONESIA (PERSERO) TBK. SEBELUM DAN SELAMA PANDEMI COVID-19 - Dwi Haryono Wiratno; Rahmawati Hanny Yustrianthe (Jurnal Akuntansi, 2023)
The study aims to determine the differences in the financial performance of PT Bank Rakyat Indonesia (Persero) Tbk. before the covid-19 pandemic and during the covid-19 pandemic as measured using NPL, BOPO, ROA, ROE, and LDR ratios. The sample used in this study is the financial statements of PT Bank Rakyat Indonesia (Persero) Tbk. for the fisrt quarter of 2017 to the fourth quarter of 2022 with a population of 24. This study uses secondary data in the form of financial statements obtained from the website www.bri.co.id and www.idx.co.id. The method used is descriptive comparative using SPSS statistical software. The result of the study using paired sample t-test show that there is a difference in average financial performance before the covid-19 pandemic with average financial performance during the covid-19 pandemic.